Engineering Polysaccharide-Based Hydrogel Photonic Constructs From Multiscale Detection to the Biofabrication of Living Optical Fibers - Guimarães, Carlos F (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2021 Wiley-VCH GmbH.